2019
DOI: 10.1111/1742-6723.13304
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Emergency endotracheal intubation in non‐traumatic brain pathologies: A systematic review and meta‐analysis

Abstract: Endotracheal intubation is an advanced airway procedure performed in the ED and the out-ofhospital setting for acquired brain injuries that include non-traumatic brain pathologies such as stroke, encephalopathies, seizures and toxidromes. Controlled trial evidence supports intubation in traumatic brain injuries, but it is not clear that this evidence can be applied to nontraumatic brain pathologies. We sought to analyse the impact of emergency intubation on survival in non-traumatic brain pathologies and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Strokes account for 10% of deaths worldwide [1]. Rapid Sequence intubation (RSI) is used in the emergency setting to improve survival in strokes, with perhaps 6 to 79% of strokes receiving intubation, depending on the stroke type [2]. Rapid sequence intubation is used to secure the airway using sedative and paralytic drugs to facilitate endotracheal intubation [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strokes account for 10% of deaths worldwide [1]. Rapid Sequence intubation (RSI) is used in the emergency setting to improve survival in strokes, with perhaps 6 to 79% of strokes receiving intubation, depending on the stroke type [2]. Rapid sequence intubation is used to secure the airway using sedative and paralytic drugs to facilitate endotracheal intubation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid Sequence intubation (RSI) is used in the emergency setting to improve survival in strokes, with perhaps 6 to 79% of strokes receiving intubation, depending on the stroke type [2]. Rapid sequence intubation is used to secure the airway using sedative and paralytic drugs to facilitate endotracheal intubation [2]. Strokes form 37% of RSI for non-traumatic brain pathologies undertaken by paramedics in Victoria, Australia [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid sequence intubation (RSI) is used in the emergency setting to protect the airway in strokes, with perhaps 6–79% of strokes receiving intubation, depending on the stroke type 2 . RSI is used to secure the airway using sedative and paralytic drugs to facilitate endotracheal intubation 2 . Stroke patients form 37% of RSI undertaken by paramedics in Victoria, Australia 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Stroke patients form 37% of RSI undertaken by paramedics in Victoria, Australia 3 . Despite the not‐infrequent use of RSI in unconscious out‐of‐hospital stroke patients, no high‐quality evidence exists to support the use of RSI for strokes 2–5 . However, a recent propensity‐matched cohort study of paramedic RSI found decreased odds of survival for RSI in both haemorrhagic and ischaemic strokes 4 .…”
Section: Introductionmentioning
confidence: 99%